Coordination‐Induced Spin‐State Switching of an Aminyl‐Radical‐Bridged Nickel(II) Porphyrin Dimer between Doublet and Sextet States. Issue 15 (12th March 2019) - Shimizu, Daiki; Ide, Yuki; Ikeue, Takahisa; Osuka, Atsuhiro
Abstract: A bis(Ni II ‐porphyrinyl)aminyl radical with meso ‐C6 F5 groups was prepared as a spin‐delocalized stable aminyl radical with a doublet spin state. Upon addition of pyridine, both Ni II centers became hexacoordinated by accepting two axial pyridines, which triggered a spin‐state change of the Ni II centers from diamagnetic ( S= 0) to paramagnetic ( S= 1). The resulting high‐spin Ni II centers interact with the aminyl radical ferromagnetically to give rise to an overall sextet state ( S= 5/2). Importantly, this coordination‐induced spin‐state switching can be conducted in a reversible manner, in that washing of the high‐spin radical with aqueous hydrochloric acid regenerates the original doublet radical in good yield. Abstract : Flick the switch : An aminyl radical bridged Ni II ‐porphyrin dimer is a doublet ( S= 1/2) but can be reversibly switched to a sextet ( S= 5/2) upon addition of pyridine ligands by coordination‐induced spin‐state switch (CISSS) owing to ferromagnetic interaction between the high‐spin Ni II centers and aminyl radical.